Las actividades lúdicas y el aprendizaje de la comunicación oral y escrita de los estudiantes de cuarto año de Educación General Básica de la Escuela “Miguel Riofrío” de la ciudad de Loja, período lectivo 2021-2022. Propuesta alternativa - Guaicha Cabrera, Johanna de los Ángeles (2022)
This research work entitled "The recreational activities and the learning of oral and written communication of the fourth-year students of Basic General Education of the "Miguel Riofrío" School, city of Loja in the 2021-2022 academic period. Alternative proposal”, starts from the problem of the low implementation of ludic activities in the learning process of oral and written communication. Its main objective is to determine the importance of recreational activities in the learning of oral and written communication in fourth-year students of Basic General Education of the "Miguel Riofrío" School, city of Loja, in the 2021-2022 academic period. The type of study was descriptive; the used methods were: scientific, descriptive, analytical, inductive, deductive and synthetic; in the same way, the techniques applied in the research work were the directed interview to the teacher and the survey applied to the students, with its instrument the questionnaire, as well as the collection of statistical and graphic data. It is concluded that, recreational activities are very important for the learning process of oral and written communication of students, due to their quality of being comprehensive and fun. Finally, as a result of this research work, an alternative proposal for recreational activities was developed that considered on games as power that stimulates the learning of oral and written communication in fourth-year students of Basic General Education, in order students can acquire language skills and abilities for autonomous development in the family, school and social environment. Keywords: students, recreational activities, learning, oral and written communication, innovation.